CHARACTERISTICS OF NEONATAL MORTALITY AND ASSOCIATED FACTORS AT CA MAU OBSTETRICS AND PEDIATRICS HOSPITAL, 2021–2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe in-hospital neonatal mortality and analyze selected associated factors among neonates treated at Ca Mau Obstetrics and Pediatrics Hospital from 2021 to 2025.Methods: A retrospective cross-sectional study was conducted using medical records of 14,453 neonates treated between January 2021 and December 2025. In-hospital neonatal mortality and related clinical conditions were extracted from records. Associations were analyzed using multivariable logistic regression.Results: The in-hospital neonatal mortality rate among treated neonates was 2.01%. Multivariable logistic regression analysis revealed that factors independently associated with neonatal mortality included respiratory distress (aOR = 5.82; 95% CI: 4.42–7.66), congenital anomalies (aOR = 4.28; 95% CI: 2.68–6.83), prematurity (aOR = 4.12; 95% CI: 3.18–5.34), neonatal infection (aOR = 3.68; 95% CI: 2.82–4.80), and early neonatal age of 0–7 days (aOR = 1.92; 95% CI: 1.38–2.67), all with p < 0.05. Male sex lost its statistical significance after multivariable adjustment.Conclusion: The in-hospital neonatal mortality rate was 2.01%. Respiratory distress, congenital anomalies, prematurity, neonatal infection, and early neonatal age were important associated factors. These findings should be interpreted as associations rather than causal risk factors.
Keywords: neonatal mortality, respiratory distress, neonatal infection, prematurity, congenital anomalies, logistic regression.